2020
DOI: 10.3390/ijms21051646
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Relieves Heat Stress-Induced Damage in Mouse Kidneys: Involvement of Antiapoptotic PKM2-AKT and Autophagic HIF-1α Signaling

Abstract: Heat stress can particularly affect the kidney because of its high rate of adenosine triphosphate consumption. Competition between apoptosis and autophagy-mediated survival always exists in damaged tissue. And Hsp90 can enhance cellular protection to resist heat stress. However, the relationship between Hsp90 and the above competition and its underlying mechanism in the kidney are unclear. The present study found that heat stress induced obvious histopathological and oxidative injury, which was connected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Among them, the expression of ciRNA1282 (HIF1A) was significantly changed in Sum1 compared with Spr2, and it binds to multiple miRNAs. Chen et al [ 44 ] found that Hsp90 relieves heat-stress-induced damage by involvement of autophagic HIF-1α signaling, which suggested that HIF1A might alleviate the damage caused by heat stress in animals. Moreover, ciRNA1282 (HIF1A) might bind to the bta-let-7 family, in which Bta-let-7c has been shown to promote adipocyte proliferation and inhibit adipocyte differentiation by acting as a sponge for circFUT10 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the expression of ciRNA1282 (HIF1A) was significantly changed in Sum1 compared with Spr2, and it binds to multiple miRNAs. Chen et al [ 44 ] found that Hsp90 relieves heat-stress-induced damage by involvement of autophagic HIF-1α signaling, which suggested that HIF1A might alleviate the damage caused by heat stress in animals. Moreover, ciRNA1282 (HIF1A) might bind to the bta-let-7 family, in which Bta-let-7c has been shown to promote adipocyte proliferation and inhibit adipocyte differentiation by acting as a sponge for circFUT10 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that PKM2 acts as an anti-apoptotic factor against the AKT signaling pathway, which controls the cell survival and apoptosis [ 50 ]. It was reported that PKM2 could efficiently attenuate heat stress-induced damage in mouse kidneys through regulating the AKT and HIF-1α signaling pathway [ 51 ]. Knockdown of PKM2 can induce autophagic cell death in prostate cancer cells through affecting the AKT/mTOR signaling pathway [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PKM2-Akt signaling is also known to activate HSP70. This evidence suggests that HSP90 mainly favors tubular cell survival by the inhibition of key apoptotic mediators and by the induction of autophagy and denotes a new insight of cross-talk between different HSPs [ 124 ].…”
Section: Heat Shock Proteins and Sirtuins As Renal Biomarkers Of Prot...mentioning
confidence: 99%